Аналіз роботи пневмомеханічного висівного апарата з периферійним розташуванням комірок - Васильковська, К. В.; Петренко, М. М.; Гончарова, С. Я.; Vasylkovska, Ekaterina; Petrenko, Nikoly; Goncharova, Svetlana (КНТУ, 2013)
Проведено аналіз роботи пневмомеханічного висівного апарата з периферійним розташуванням комірок. Доведено, що для гарантованого сходження зайвого насіння відцентрова сила повинна перевищувати силу тяжіння насінини. Складено диференційне рівняння руху частки в полі діючих сил, при вирішенні якого отримано залежності переміщення частки по лопатці від кута обертання диску при різних кутових швидкостях. Analysis of the design of the proposed sowing device suggests a possibility of capture, seeds, movement and dumping them , even without the use of vacuum. But guaranteed to shift the main seed furrow necessary to use more force that it be kept in the cell. Found that to guarantee convergence excess seed centrifugal force must exceed the force of gravity seed. Done differential equation of motion particle in the field of active forces in dealing with any dependencies particles moving in a pan on the angle of rotation of the disk at different angular velocities. The presence of suction power , can increase the size of the cavity passive trunk seed to 0.26 ... 0.30 radians in angular velocity of the disk 30 ... 25 radians per second. This will guaranteed to remove those extra seeds , as they move around the pan more than half their own diameter. A basic seed, thanks to the force of suction , securely held in a cell and transported to the area of a disk reset.
Analysis of pneumomechanical sowing device with a peripheral cells
Keywords: висівний апарат; комірка; лопатка; сила присмоктування; переміщення насінини